(3eHGOF GdGbJUGO GdLRFjs - (3eMeO eMehO(B, (3GdfUQs ((3YeGf(B:s (3OGQ GdCed(B,s, 1989)
(3eaGgje YGeI,eG gh GdGbJUGO,GdWdH hGdYQV,GdeQhfI,Sdhc GdeSJgdc,GdGfJGL hGdJcGdja,GdefGaSI GdcGedI,GdGMJcGQ GdJGe,GdefGaSI GdGMJcGQjI,GMJcGQ GdbdI,Shb YfGUQ GdGfJGL,ehGVjY NGUIs
(3GdeUWdMGJ HGdCfLdjRjI U(B.374s
Keywords: (3GdGbJUGO GdLRFjs